A geometric algebra approach to determine motion/constraint, mobility and singularity of parallel mechanism. (October 2017) - Huo, Xinming; Sun, Tao; Song, Yimin
Highlights: The motions, constraints and their relations are represented in a concise form by employing the characterized geometric elements with CGA. The mobility of parallel mechanism in common situations is obtained by geometric entities calculation and linear independency determination. The singularity of parallel mechanism is identified by two indices based on the shuffle and outer products. A typical example is given to illustrate the motions/constraints, mobility and singularity analysis. Abstract: The crucial procedure of mobility and singularity identification of parallel mechanisms is widely recognized as how to determine their motions (constraints) concisely and visually. In this paper, we propose a geometric algebra (GA) based approach to determine the motions/constraints, mobility and singularity of parallel mechanisms mainly utilizing the geometric and algebraic relations. Firstly, the motions, constraints and their relations are represented by conformal geometric algebra (CGA) formulas in a concise form by employing the characterized geometric elements with G 4, 1 . Secondly, the mobility of parallel mechanism, including its number and property and the axes of motions, not only at origin configuration but also in the prescribed workspace, is obtained by the procedure proposed in this paper. Thirdly, the singularity of parallel mechanism is identified by the two indices proposed in this paper with shuffle and outer products. Finally, a typical example is given to illustrate the motions/constraints, mobility and singularity analysis. This approach is beneficial to kinematic analysis and optimal design of parallel mechanisms, especially for which would be carried out in automatic and visual manner using computer programming languages.